Death within the first year after kidney transplantation – an observational cohort study. (14th November 2013) - Farrugia, Daniela; Cheshire, James; Begaj, Irena; Khosla, Sajan; Ray, Daniel; Sharif, Adnan
Summary The risk of death within the first year postkidney transplantation is not well described in the contemporary era. We extracted data on all kidney transplant procedures performed in England between April 2001 and March 2012. Data linkage analysis was performed between Hospital Episode Statistics and the Office for National Statistics to identify all deaths. Cox proportional hazard models were performed to identify factors associated with 1‐year mortality. 566 deaths (3.0%) occurred within the first year post‐transplant (from 19 103 kidney transplant procedures analysed). Infection, cardiovascular events and malignancy were classified in 21.6%, 18.3% and 7.4% of death certificates, respectively. Among recipients with prior myocardial infarct history who died within the first year, 38.8% of deaths were attributed to a cardiac‐related event. Malignancy‐related death was responsible for 61.5% of 1‐year mortality for allograft recipients with pretransplant cancer history. 22.1% of deaths included kidney failure as a contributory factor on the death certificate (3.3% specifically stated allograft failure). Variables associated with 1‐year mortality included deceased‐donor kidney, increasing age, residence in socioeconomically deprived area and history of select medical comorbidities pre‐operatively. We conclude 1‐year mortality postkidney transplantation is low, but in select allograft recipients, the risk of death increases considerably.